(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
Parents ’ foster pattern is an active role for parents on the development of their children. Especially when they are still in the pre-school stage, to increase self-reliance on children there are 3 kinds of foster pattern namely democratic, authoritarian, permissive. The purpose of this research is to analyse the relationship between mother’s foster patterns that work with self-reliance on children. The design of this research is correlated with a cross sectional approach, sample selection with purposive sampling. The research was conducted from October 2019 to April 2020 with data collection in March 2020 using questionnaire at 176 mothers Desa Tualang Kec. Tualang Kab.Siak. Data processing and variable dependent.. The test results statistic obtained a significant relationship between mother’s foster pattern working with the child’s self-reliance level, with a value of P value = 0.011 < a = 0.05. With a good democratic foster pattern of 134 respondents who have children with a very independent level of self-reliance. Based on the results of these studies the researchers suggest that health works provide parenting training to mother’s so they can broaden their horizons in educating and caring for their children.